Tumor-related molecular determinants of neurocognitive deficits in patients with diffuse glioma. Issue 10 (11th February 2022) - van Kessel, Emma; Berendsen, Sharon; Baumfalk, Anniek E; Venugopal, Hema; Krijnen, Eva A; Spliet, Wim G M; van Hecke, Wim; Giuliani, Fabrizio; Seute, Tatjana; van Zandvoort, Martine J E; Snijders, Tom J; Robe, Pierre A
Abstract: Background: Cognitive impairment is a common and debilitating symptom in patients with diffuse glioma, and is the result of multiple factors. We hypothesized that molecular tumor characteristics influence neurocognitive functioning (NCF), and aimed to identify tumor-related markers of NCF in diffuse glioma patients. Methods: We examined the relation between cognitive performance (executive function, memory, and psychomotor speed) and intratumoral expression levels of molecular markers in treatment-naive patients with diffuse glioma. We performed a single-center study in a consecutive cohort, through a two-step design: (1) hypothesis-free differential expression and gene set enrichment analysis to identify candidate oncogenetic markers for cognitive impairment. Nineteen molecular markers of interest were derived from this set of genes, as well as from prior knowledge; (2) correlation of cognitive performance to intratumoral expression levels of these nineteen molecular markers, measured with immunohistochemistry. Results: From 708 included patients with immunohistochemical data, we performed an in-depth analysis of neuropsychological data in 197, and differential expression analysis in 65 patients. After correcting for tumor volume and location, we found significant associations between expression levels of CD3 and IDH-1 and psychomotor speed; between IDH-1, ATRX, NLGN3, BDNF, CK2Beta, EAAT1, GAT-3, SRF, and memory performance; and between IDH-1, P-STAT5b, NLGN3, CK2Beta, and executive functioning. P-STAT5b, CD163, CD3, and Semaphorin-3A were independently associated after further correction for histopathological grade. Conclusion: Molecular characteristics of glioma can be independent determinants of patients' cognitive functioning. This suggests that besides tumor volume, location, and histological grade, variations in glioma biology influence cognitive performance through mechanisms that include perturbation of neuronal communication. These results pave the way towards targeted cognition improving therapies in neuro-oncology.